Targeting Long Noncoding RNA in Glioma: A Pathway Perspective - Junyang Li; Yihao Zhu; Handong Wang; Xiangjun Ji (Elsevier, 2018)
Long noncoding RNAs (lncRNAs) participate extensively in biological processes of various cancers. The majority of these transcripts are uniquely expressed in differentiated tissues or specific cancer types. lncRNAs are aberrantly expressed in gliomas and exert diverse functions. In this article, we provided an overview of how lncRNAs regulate cellular processes in glioma, enumerated the lncRNAs that may act as glioma biomarkers, and showed their potential clinical implications. Keywords: long noncoding RNA, glioma, biomarker